Determining factors in the sexual division of labor in the Costa Rican textile industry (1960-1980) - Merienne, Florence (2020)
The following article aims to identify the determining factors in the sexual division of labor in the Costa Rican textile industry strongly feminized between 1960 and 1980, a time of boom in textile production in this country. The analysis of primary sources of various kinds revealed the diversity of the factors and actors involved. The investigation is based on the examination of the worksheets of several companies in the textile sector, of files for union persecution, of journalistic sources and of the National Professional Learning Institute. Interviews with women workers and employers and literature were also used to reconstruct the socio-cultural context. From this research, it appears that even in a context of labor shortages in the Costa Rican textile industry, employers do not renounce their gender vision and continue to organize work around the gender category. Legal norms, family models, unions also inherit this gender vision and in turn contribute to perpetuating this sexual division of labor. Patriarchy and capitalism mutually nurture each other in this process, resulting for women a subordinate place in the production process, which translates into strong wage inequalities to the detriment of women workers. Although feminist organizations exist to question this vision, they are unable to transform their demands into a collective movement of national importance.